2006
DOI: 10.1086/505098
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Postsurgical Meningitis in Children A 12-Year Survey Comparing Data From 1993-1998 With Data From 1999-2004

Abstract: Nosocomial Postsurgical Meningitis in Children:A 12-Year Survey Comparing Data From 1993-1998 With Data From 1999-2004 TO T H E EDITOR-The incidence of nosocomial meningitis after neurosurgery is increasing. 12 In a previous study, a survey of all 8 pediatric and neonatal neurosurgery departments in Slovakia revealed that 101 cases of pediatric bacterial meningitis were recorded during 1993-1998, with an attributable mortality of 15% and sequelae detected in 18% of cases. 1 We conducted a similar survey durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…By contrast, in a review of four studies comprising 281 adult patients with hospital-acquired bacterial meningitis, 3.6% (ten patients) had meningitis due to Acinetobacter spp 5,7,8,12. The authors of one evaluation of children with nosocomial meningitis reported that acinetobacter accounted for 11.2% (20/178) of cases 13. In large series in the USA and Taiwan, acinetobacter ranked the fifth most common genus to be associated with nosocomial meningitis 5,8.…”
Section: Clinical Characteristicsmentioning
confidence: 96%
“…By contrast, in a review of four studies comprising 281 adult patients with hospital-acquired bacterial meningitis, 3.6% (ten patients) had meningitis due to Acinetobacter spp 5,7,8,12. The authors of one evaluation of children with nosocomial meningitis reported that acinetobacter accounted for 11.2% (20/178) of cases 13. In large series in the USA and Taiwan, acinetobacter ranked the fifth most common genus to be associated with nosocomial meningitis 5,8.…”
Section: Clinical Characteristicsmentioning
confidence: 96%
“…Other studies have reported S.aureous as the most frequent organism, a lot of results related to nosocomial and post-surgical meningitis [2,10,18,19] . Some other studies have demonstrated Streptococcus pneumonia is the most common pathogen in post-surgical meningitis [6] , however the incidence of S. pneumonia observed more in the children [12] . Parodi and co-workers reported that the proportion of cases of nosocomial meningitis due to gram-negative organisms appears to be increasing, they revealed the entrobacters grew rapidly as the cause of nosocomial meningitis [11] .…”
Section: Discussionmentioning
confidence: 99%
“…The authors of one evaluation of children with nosocomial meningitis reported that Acinetobacter accounted for 11.2% (20/178) of cases [5]. In large series in the USA and Taiwan, Acinetobacter ranked the fifth most common genus to be associated with nosocomial meningitis [15,16]. Nosocomial infections associated with Acinetobacter baumannii lead to high mortality [17].…”
Section: Discussionmentioning
confidence: 99%